Canonical failure modes of real-time control systems: insights from cognitive theory. Issue 6 (25th April 2016) - Wallace, Rodrick
Abstract : Newly developed necessary conditions statistical models from cognitive theory are applied to generalisation of the data-rate theorem for real-time control systems. Rather than graceful degradation under stress, automatons and man/machine cockpits appear prone to characteristic sudden failure under demanding fog-of-war conditions. Critical dysfunctions span a spectrum of phase transition analogues, ranging from a ground state of 'all targets are enemies' to more standard data-rate instabilities. Insidious pathologies also appear possible, akin to inattentional blindness consequent on overfocus on an expected pattern. Via no-free-lunch constraints, different equivalence classes of systems, having structure and function determined by 'market pressures', in a large sense, will be inherently unreliable under different but characteristic canonical stress landscapes, suggesting that deliberate induction of failure may often be relatively straightforward. Focusing on two recent military case histories, these results provide a caveat emptor against blind faith in the current path-dependent evolutionary trajectory of automation for critical real-time processes.